STUDY OF MARKERS OF ANTIOXIDANT PROTECTION OF THE ORAL CAVITY IN THE ORAL FLUID OF PATIENTS WITH PERI-IMPLANTITIS AGAINST THE BACKGROUND OF THE TREATMENT AND PREVENTION COMPLEX - Hurtova, Y.M.; Shnaider, S.A.; Dienha, O.V.; Strochenko, Ye.O.; Хороз, Л.М.; Topov, I.H.; Rachynskyi, S.V. (World of Medicine and Biology, 2024)
The study was devoted to researching the effect of a therapeutic and prophylactic complex on biochemical markers of bone tissue in rats with peroxidative periodontitis and protein deficiency. The experiment included 30 Wistar male rats divided into three groups: an intact group, a group with combined pathology, and a group with combined pathology receiving the therapeutic and prophylactic complex. In the bone tissue homogenates of the animals, the activity of alkaline and acid phosphatases was determined as markers of osteoblastic and osteoclastic activity, respectively. The therapeutic and prophylactic complex led to a significant increase in the mineralization index and a reduction in alveolar bone atrophy, exceeding the results observed in the group with untreated combined pathology. This improvement in bone tissue indicators suggests the therapeutic complex’s potential to restore bone formation processes and suppress resorptive activity, highlighting its applicability for preventing bone tissue degradation under conditions of nutritional deficiencies and oxidative stress.
Keywords: periodontitis; bone tissue; rats; experiment; biochemical markers